Six unusual Cladotanytarsus Kieffer: towards a systematics of the genus and resurrection of Lenziella Kieffer (Diptera: Chironomidae: Tanytarsini) - Giłka, Wojciech (Zootaxa, 2011)
Following the inclusion of Lenziella Kieffer, 1922 into Cladotanytarsus Kieffer, 1921, the genus consists of two subgenera: Cladotanytarsus s. str. (type species: C. pallidus Kieffer, 1922) and Lenziella Kieffer, 1922 (type species: L. bicornuta Kieffer, 1922). Six species of the subgenus Lenziella known from the Holarctic region are diagnosed and reviewed. Lectotype of Cladotanytarsus wexionensis Brundin, 1947 is designated, and the name is treated as a synonym of Cladotanytarsus (L.) bicornutus Kieffer, 1922 in a new combination. Cladotanytarsus (L.) amandus Hirvenoja, 1962 (male) and C. (L.) crusculus (Sæther, 1971) (male, female, pupa) are redescribed. Cladotanytarsus (L.) latissimus sp. nov. (male, female, pupa), C. (L.) piniger sp. nov. (male), and C. (L.) subletteorum sp. nov. (male, female, pupa) are described. Keys to adults and pupae of Lenziella as well as data on biology of the species are presented.